2016
DOI: 10.3389/fnhum.2016.00560
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Alternating Current Stimulation at Beta Frequency: Lack of Immediate Effects on Excitation and Interhemispheric Inhibition of the Human Motor Cortex

Abstract: Transcranial alternating current stimulation (tACS) is a form of noninvasive brain stimulation and is capable of influencing brain oscillations and cortical networks. In humans, the endogenous oscillation frequency in sensorimotor areas peaks at 20 Hz. This beta-band typically occurs during maintenance of tonic motor output and seems to play a role in interhemispheric coordination of movements. Previous studies showed that tACS applied in specific frequency bands over primary motor cortex (M1) or the visual co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
2
17
0
1
Order By: Relevance
“…However, previous studies report heterogeneous results for 20 Hz tACS applied over the motor cortex area. Our results are in line with several other studies that did not find stimulation effects on motor cortex excitability [ 45 , 46 ], while Cappon et al (2016) demonstrated inhibitory effects following 20 Hz stimulation [ 47 ]. Unlike Cappon (2016), we did not use a task during stimulation; this activation during stimulation might influence the effects of tACS, since previous studies showed state-dependent effects of tACS [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, previous studies report heterogeneous results for 20 Hz tACS applied over the motor cortex area. Our results are in line with several other studies that did not find stimulation effects on motor cortex excitability [ 45 , 46 ], while Cappon et al (2016) demonstrated inhibitory effects following 20 Hz stimulation [ 47 ]. Unlike Cappon (2016), we did not use a task during stimulation; this activation during stimulation might influence the effects of tACS, since previous studies showed state-dependent effects of tACS [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…During rest with eyes open, alpha activity was significantly increased after 10 Hz tACS and 20 Hz tACS as we have gathered based on the literature ( Zaehle et al, 2010 ) whereas beta band activity stayed unaffected. Furthermore, we hypothesized that parietal 10 Hz tACS evoke synchronized oscillatory activity in the alpha range that lead to reduced interhemispheric interaction and deterioration in bimanual coordination performance ( Serrien and Brown, 2002 ) whereas 20 Hz tACS would promote the natural beta oscillation of bimanual coordination ( Rjosk et al, 2016 ) that leads to an enhanced performance. Contrary to our expectations, parietal alpha activity increased significantly after both stimulation frequencies which was accompanied by significant decreases in ΔHboxy concentrations right hemispheric whereas bimanual motor performance and beta band activity stayed unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…One approach might be the ambiguous mechanisms underlying bimanual coordination. Rjosk et al (2016) demonstrated that beta-band activity plays a crucial role in interhemispheric coordination of movements ( Rjosk et al, 2016 ). Additionally, Davis et al (2012) suppose that motor control is associated with synchronized oscillatory activity at beta frequency, whereby voluntary movements are associated with suppressed beta band activity (desynchronization) ( Davis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations